Improved responses to pegylated interferon alfa-2b and ribavirin by individualizing treatment for 24-72 weeks - Sarrazin, Christoph; Schwendy, Susanne; Möller, Bernd; Dikopoulos, Nektarios; Buggisch, Peter; Encke, Jens; Teuber, Gerlinde; Goeser, Tobias; Thimme, Robert; Klinker, Hartwig; Boecher, Wulf O.; Schulte-Frohlinde, Ewert; et al. (Gastroenterology, 2011)
Background & Aims - Guidelines recommend that patients with chronic hepatitis C virus (HCV) infection be treated with pegylated interferon and ribavirin for 24, 48, or 72 weeks, based on their virologic response to treatment. We investigated the effects of treating patients for individualized durations. - Methods - We treated 398 treatment-naïve patients who had HCV genotype 1 infections with pegylated interferon alfa-2b and ribavirin for 24, 30, 36, 42, 48, 60, or 72 weeks (mean of 39 weeks, termed individualized therapy); the duration of therapy was determined based on baseline viral load and the time point at which HCV RNA levels became undetectable (measured at weeks 4, 6, 8, 12, 24, and 30). Results were compared with those of 225 patients who received standard treatment for 48 weeks (mean of 38 weeks). - Results - Rates of sustained virologic response (SVR) were 55% among patients who received individualized treatment and 48% among those who received standard treatment (P < .0001 for noninferiority). SVR rates, according to the time point at which HCV RNA levels became undetectable, did not differ significantly between groups. Patients with a rapid virologic response (undetectable levels of HCV RNA at week 4) who were treated for 24 to 30 weeks achieved high rates of SVR (86%-88%). Rates of SVR increased among slow responders who first tested negative for HCV RNA at week 24 and were treated for 60 to 72 weeks compared with those treated for 48 weeks (60%-68% vs 43%-44%). The CC polymorphism at IL28B rs129797860 was associated with an increased rate of SVR compared with the CT/TT polymorphism (P < .0001) at baseline but not among patients who had undetectable levels of HCV RNA following treatment. - Conclusions - Individualizing treatment of patients with chronic HCV genotype 1 infections for 24 to 72 weeks results in high rates of SVR among rapid responders and increases SVR among slow responders.
Gesehen am 06.10.2022